A Carbon‐Carbon Bond Cleavage‐Based Prodrug Activation Strategy Applied to β‐Lapachone for Cancer‐Specific Targeting. Issue 40 (23rd August 2022) - Gong, Qijie; Li, Xiang; Li, Tian; Wu, Xingsen; Hu, Jiabao; Yang, Fulai; Zhang, Xiaojin
Abstract: Prodrugs are one of the most common strategies for the design of targeted anticancer agents. However, their application is often hampered by the modifiable groups available on parent drugs. Herein, a carbon‐carbon (C−C) bond cleavage‐based prodrug activation strategy is reported, which was successfully used to design prodrugs of β‐lapachone (β‐lap), an ortho ‐quinone natural product without traditional modifiable groups for the construction of C−N/C−O bond cleavage‐based prodrugs. The designed β‐lap prodrug with a reactive oxygen species‐specific trigger was quickly activated, releasing β‐lap. It exerted anticancer efficacy via NAD(P)H:quinone oxidoreductase 1 (NQO1)‐mediated futile redox cycling, resulting in potent cytotoxicity that was highly selective for NQO1‐rich cancer cells over normal cells both in vitro and in vivo. This significantly amplified the therapeutic window of β‐lap. This study provides a practical strategy for the design of prodrugs for parent drugs that do not contain traditional modifiable groups. Abstract : A C−C bond cleavage‐based prodrug activation strategy is described and applied to β‐lapachone for cancer‐specific targeting. The prodrug is activated through the cleavage of the C−C bond and releases β‐lapachone for treating NAD(P)H:quinone oxidoreductase 1 (NQO1)‐overexpressing cancers. This strategy provides a valuable addition to the existing prodrug strategies.